Are the 2009 Institute of Medicine gestational weight gain recommendations applicable in a contemporary South-East Asian pregnancy cohort? Results of a prospective analysis - Yong Ting Tai; Jun Kit Khoo; Quan Hziung Lim; Lee-Ling Lim; Sharmila Sunita Paramasivam; Jeyakantha Ratnasingam; Nicholas Ken Yoong Hee; Tharsini Sarvanandan; Ying Guat Ooi; Victoria Wei Fang Boey; Saravanaa Nalliah; Peng Chiong Tan; et al. (PLoS ONE, 2025)
Gestational Weight Gain (GWG) modulates pregnancy outcomes and long-term offspring metabolic health. The 2009 Institute of Medicine (IOM) GWG recommendations have largely been validated in Caucasian and mono-ethnic East Asian cohorts. Asians are at higher metabolic risk at a lower body mass index (BMI), and this has prompted the World Health Organization (WHO) to identify lower BMI cut-offs for risk evaluation amongst Asians. This prospective observational cohort study aimed to determine if 2009 IOM GWG thresholds are applicable in a contemporary multi-ethnic South-East Asian cohort. We recruited 875 mothers from an urban Malaysian tertiary clinic during screening for gestational diabetes mellitus (GDM) from 2014–2021. Data collected included measures of insulin-sensitivity, total GWG (maternal weight at delivery–self-reported pre-gravid weight), and neonatal anthropometrics (birthweight and skinfold-thickness measured with Harpenden calipers). BMI was stratified by Caucasian (overweight ≥25kg/m2, obese ≥30kg/m2) as well as Asian (overweight ≥23kg/m2, obese ≥27.5kg/ m2) cut-offs, and patients categorized by 2009 IOM GWG reference ranges. The cohort comprised 67% Malay-, 23% Chinese- and 10% Indian-descent mothers with a high prevalence of overweight/obesity (Asian cut-offs 56.9% vs Caucasian 44%). When Asian BMI cut-offs were deployed, excessive GWG incidence increased (34.1% → 40.6%) whilst inadequate GWG declined (30% → 24.8%) (p<0.05). Upon multivariate-analysis (adjusting for age, parity, race, GDM, insulin-sensitivity, baby-gender) excessive GWG categorized with Caucasian BMI cut-offs was significantly associated with increased risk of macrosomia (adjusted odds ratio (aOR) 8.65, 95% confidence interval (CI) 1.07–70.01), Neonatal-Fat-Mass (NFM) >90th centile (aOR 2.14, 95% CI 1.02–4.45) and Sum-of-Skinfold Thickness (SSFT) >90th centile (aOR 3.88, 95% CI 1.77–8.51). Excessive GWG by Asian cut-offs was also associated with increased risk of SSFT >90th centile (aOR 5.75, 95% CI 2.35–14.10). Inadequate GWG by both Caucasian and Asian BMI cut-offs was associated with Small-for-Gestational-Age (SGA) status (aOR 4.30, 95% CI 2.48–7.45 and aOR 3.66, 95% CI 2.13–6.30 respectively). In conclusion, the 2009 IOM GWG recommendations, using either Caucasian or regional Asian BMI cut-offs, are applicable in a contemporary Malay majority South-East Asian cohort in terms of predicting abnormal neonatal adiposity. Importantly, the association with neonatal adiposity is independent of increased maternal insulin resistance characteristic of Asians.